Padrões fenológicos e dispersão de diásporos de espécies anemocóricas representativas do Cerrado - Novaes, Letícia Rodrigues (2020)
In seasonal environments, biotic and abiotic factors vary between seasons. Plants evolved adaptations to express their phenophases in periods with more suitable conditions. Previous studies have described a generalized phenological pattern for all species in the Brazilian savanna, mainly based on rainfall and temperature, not considering the wind, the dispersal mode and the division between the phenophases of young and ripe fruits. The wind is important especially at the diaspore release and its dispersal distance, observed in anemocoric species. Distance affects plant reproductive success, species distribution pattern, population dynamics, and community structure. Despite this, there is no consensus about which factors are the most important in driving seed dispersal distance. Most studies are performed with Northern Hemisphere vegetation and few studies have attempted to observe anemocoric seed dispersal distances of plants from the Southern Hemisphere, especially at Savanna environments. The Brazilian Savanna, also called Cerrado, presents about 30% of anemocoric species. Furthermore, rare studies concurrently evaluate the influence of biotic and abiotic factors and their interactions on dispersal distance under natural and controlled conditions. In this context, the first aim was to describe the phenological patterns of five anemocoric plant species in the face of different climatic conditions. We addressed three hypotheses: (i) anemocoric plants are phenologically similar; (ii) the influence of abiotic factors (wind, rainfall, temperature, and humidity) differs between phenophases; (iii) diaspores dispersal is related to deciduousness. The second aim was to investigate the influence of extrinsic and intrinsic seed-related factors on the seed dispersal distances of anemocoric species under natural (field) and controlled (laboratory with wind tunnel) conditions. Our main hypothesis was that both extrinsic (wind speed and temperature) and intrinsic (falling time, wing-loading and aerodynamic group) diaspore-related factors influence diaspore dispersal distance of Cerrado anemocoric species. The results show that the species are phenologically similar, except for the floral bud and flower of two species and young fruit. The influence of each abiotic variable differs between phenophases, but in general rainfall and wind are the most important factors. The diaspore dispersal moment is related to the leaf fall. The results also showed that extrinsic and intrinsic factors to diaspores directly and indirectly influenced the dispersal distance. The most relevant factor was wind, followed by falling time. The dispersal distance was positively related to the wind speed, temperature and falling time and negatively related to the diaspore wing-loading. The variables also presented interactions with each other, indirectly influencing the distance. These results show the importance of include wind and the interactions between phenophases when evaluating phenological patterns. It also suggests that linear and causal effects should be considered in order to determine the dispersal potential of anemocoric species.